Challenges and Strategies for Primary Healthcare Systems in Addressing Population Aging: An Empirical Study Based on the Integrated Care Model - Shuo Chen (Scientific Journal Of Humanities and Social Sciences, 2026)
Population ageing poses unprecedented challenges to primary health care (PHC) systems worldwide, demanding a fundamental shift from episodic, disease-centred care to continuous, person-centred integrated models. This paper reviews the challenges confronting PHC systems in responding to an ageing population and evaluates strategies grounded in integrated care frameworks. We adapt the Andersen Behavioral Model to construct a PHC capacity index that captures predisposing, enabling, and need factors specific to geriatric service delivery. Next, we quantify clinical, professional, organizational and system-level integration of care across settings by operationalizing the Rainbow Model of Integrated Care. A barrier analysis reveals four areas of barriers: workforce, financing, digital readiness and fragmented governance. Based on published information from systematic reviews and national health surveys, we estimate a composite integration readiness score, and conduct sensitivity analyses to identify the relative role of each barrier domain. Findings show that the workforce deficit and funding gaps have the greatest impact on being ready for integration, followed by digital infrastructure constraints and governance fragmentation. It also finds that these barrier domains interact multiplicatively, which means that their effect is compounding, and that the effective integration capacity is a small fraction of what it could be. Recommendations for policies involve increasing the generation of geriatric training pipelines, creating incentive systems for bundled care through the redesign of reimbursement policies, investing in interoperable health information systems and setting up governance bodies across sectors.